What to Expect When It Gets Hotter: The Impacts of Prenatal Exposure to Extreme Heat on Maternal and Infant Health - Jiyoon Kim; Ajin Lee; Maya Rossin-Slater (Institute of Labor Economics (IZA), 2019)
We use temperature variation within narrowly-defined geographic and demographic cells to show that prenatal exposure to extreme heat increases the risk of maternal hospitalization during pregnancy, and that this effect is larger for black than for white mothers. At childbirth, heat-exposed mothers are more likely to have hypertension and have longer hospital stays. For infants, fetal exposure to extreme heat leads to a higher likelihood of dehydration at birth and hospital readmission in the first year of life. Our results provide new estimates of the health costs of climate change and identify environmental drivers of the black-white maternal health gap.
Keywords: I14; I18; Q54; 330; extreme heat; maternal health; infant health